Evaluation of a hybrid capture-based pan-cancer panel for analysis of treatment stratifying oncogenic aberrations and processes - Kroeze, Leonie I.; de Voer, Richarda M.; Kamping, Eveline J.; von Rhein, Daniel; Jansen, Erik A. M.; Hermsen, Mandy J. W.; Barberis, Massimo C. P.; Botling, Johan; Garrido-Martin, Eva M.; Haller, Florian; Lacroix, Ludovic; Maes, Brigitte; et al. (The journal of molecular diagnostics, 2020)
Stratification of patients for targeted and immune-based therapies requires extensive genomic profiling that enables sensitive detection of clinically relevant variants and interrogation of biomarkers, such as tumor mutational burden (TMB) and microsatellite instability (MSI). Detection of single and multiple nucleotide variants, copy number variants, MSI, and TMB was evaluated using a commercially available next-generation sequencing panel containing 523 cancer-related genes (1.94 megabases). Analysis of formalin-fixed, paraffin-embedded tissue sections and cytologic material from 45 tumor samples showed that all previously known MSI-positive samples (n = 7), amplifications (n = 9), and pathogenic variants (n = 59) could be detected. TMB and MSI scores showed high intralaboratory and interlaboratory reproducibility (eight samples tested in 11 laboratories). For reliable TMB analysis, 20 ng DNA was shown to be sufficient, even for relatively poor-quality samples. A minimum of 20% neoplastic cells was required to minimize variations in TMB values induced by chromosomal instability or tumor heterogeneity. Subsequent analysis of 58 consecutive lung cancer samples in a diagnostic setting was successful and revealed sufficient somatic mutations to generate mutational signatures in 14 cases. In conclusion, the 523-gene assay can be applied for evaluation of multiple DNA-based biomarkers relevant for treatment selection.
Gesehen am 01.04.2021